(3GdCbVjI GdfHhjI (B( (3CbVjI QShd Gddg Udi Gddg Ydjg hSde (B)s - (3eMeO Hf GdaQL GdbQWHj GdeGdcj, CHh YHO Gddg ,GHf GdWdGY,J (B497 (3g` s ((3CMeO Hf Ydi Hf eMeO Hf GdUai s)
(3ChdgG (B:s
(3CNHQfG Gdabjg GdeTGhQ CHh YHOGddg eMeO Hf aQL bGd GdMeO ddg ceG MeO faSg hCVGa eG MeOg Ndbg gPG cJGH GPcQ ajg Cf TGA Gddg eG GfJgi Edi ef CbVjI QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3bGd CYQGHi (B: (3ahJ GdMGLI VjQ ef WdHgG ef ZjQ CgdgG hbGd BNQ YR GdfRgI CTQa ef SQhQ GdaGFOI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B328s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdMQe Gdeci (B((3MOjK (B31) s
Keywords: (3GdMOjK h GdeUWdMs